From Restriction of Freedom of Movement to Deprivation of Liberty of Persons in need of International Protection: Compliance of Serbian legislation with the European Court of Human Rights standards - Kastratović, Aleksandra (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
Persons in need of international protection are already in difficult situation due to their uncertain legal status. Until their legal status is determined, their freedom of movement can be restricted. However, the problem arises because such simple restriction of their movement can amount to deprivation of their liberty. The aim of the paper is to determine when and under what conditions can restriction on freedom of movement amount to deprivation of liberty, whether the difficult possition of persons in need of international protection is taken into account, and whether Serbian legislation implements relevant standards established in the practice of the European Court of Human Rights. The analysis suggests that, based on the provision of the Law on Asylum and Temporary Protection concerning restriction of freedom of movement of asylum seekers, there could be a practical problen. Although Serbian legislation qualifies the retention of foreigners and asylum seekers in Shelter for Foreigners as a measure of restriction of movement, such situation can be inherent to deprivation of their liberty. Because of this remark, the author proposes necessary changes at the legislative level.
Keywords: international protection; restriction of freedom of movementm; deprivation of liberty; European Court of Human Rights; Serbian legislation